Acute Treatment With Gleevec Does Not Promote Early Vascular Recovery Following Intracerebral Hemorrhage in Adult Male Rats - Abbas, Mohammed; Haddad, Elizabeth; Hamer, Mary; Nowrangi, Derek; Zhang, John; Pearce, William J.; Tang, Jiping; Obenaus, Andre (Frontiers in Neuroscience, 2020)
Intracerebral hemorrhage (ICH) remains one of the most debilitating types of stroke and is characterized by a sudden bleeding from a ruptured blood vessel. ICH often results in high mortality and in survivors, permanent disability. Most studies have focused on neuroprotective strategies designed to minimize secondary consequences and prevent further pathology. Lacking is an understanding of how ICH acutely affects cerebrovascular components and their response to therapeutic interventions. We hypothesized that ICH alters cortical vessel complexity in the parenchyma adjacent to site of the initial vascular disruption and that vascular abnormalities would be mitigated by administration of the PDGFR inhibitor, Imatinib mesylate (Gleevec). Briefly, ICH was induced in male adult rats by injection of collagenase into basal ganglia, followed by Gleevec administration (60 mg/kg) 1 hour after injury. Rats were then perfused using vessel painting methodology (Salehi et al 2018) to stain whole brain vascular networks at 1 day post ICH. Axial and coronal wide field fluorescence microscopy was performed. Analyses for vascular features were undertaken as fractal analysis for vascular complexity. Data were collected from four groups of rats: Sham+Vehicle; Sham+Gleevec; ICH+Vehicle; ICH+Gleevec. Microscopy revealed that cortical vessels in both ipsi- and contralateral hemispheres exhibited significantly reduced density and branching by 22% and 34%, respectively. Fractal measures confirmed reduced complexity as well. Gleevec treatment further reduced vascular parameters, including reductions in vessel density in tissues adjacent to the ICH. The reductions in brain wide vascular networks after Gleevec treatment in ICH is contrasted by previous reports of improved behavioral outcomes and decreased lCH lesion volumes that were assess sub-acutely. The reductions in the vascular network after Gleevec may be involved in long-term repair mechanisms by pruning injured vessels that ultimately promote new vessel growth.